Emotion-related impulsivity and suicidal ideation and behavior in schizophrenia spectrum disorder: a pilot fMRI study - Hoptman, Matthew J.; Evans, Kathryn T.; Parincu, Zamfira; Sparpana, Allison M.; Sullivan, Elizabeth F.; Ahmed, Anthony O.; Iosifescu, Dan V. (Frontiers in Psychiatry, 2024)
Suicidal ideation and behavior (SIB) are serious problems in people with schizophrenia spectrum disorders (SSD). Nevertheless, relatively little is known about the circuitry underlying SIB in SSD. Recently, we showed that elevated emotional impulsivity (urgency) was associated with SIB in SSD. Here we examined brain activity in people with SSD and elevated SIB. We tested 16 people with SSD who had low SIB and 14 people with high SIB on a task in which emotion regulation in response to affective pictures was implicitly manipulated using spoken sentences. Thus, there were neutral pictures preceded by neutral statements (NeutNeut condition), as well as negative pictures preceded by either negative (NegNeg) or neutral (NeutNeg) statements. After each picture, participants rated how unpleasant each picture was for them. The latter two conditions were compared to the NeutNeut condition. We compared the emotion-regulated condition (NeutNeg) to the unregulated condition (NeutNeut). Statistics were threshold using threshold free cluster enhancement (TFCE). People in the low SIB group showed higher activation in this contrast in medial frontal gyrus, right rostral anterior cingulate, bilateral superior frontal gyrus/DLPFC, and right middle cingulate gyrus, as well as right superior temporal gyrus. This study provides clues to the neural basis of SIB in SSD as well as underlying mechanisms..